Outcomes After Comprehensive Vision Rehabilitation Using Vision-related Quality of Life Questionnaires: Impact of Vision Impairment and National Eye Institute Visual Functioning Questionnaire. Issue 2 (February 2019) - Selivanova, Alexandra; Fenwick, Eva; Man, Ryan; Seiple, William; Jackson, Mary Lou
Abstract : SIGNIFICANCE: This research is significant because, although vision-related quality of life (VRQoL) is improved after vision rehabilitation (VR), patients with certain characteristics respond less positively on VRQoL measures, and this should inform future care. PURPOSE: The purposes of this study were to evaluate how two VRQoL questionnaires compare in measuring change in patient-reported outcomes after VR and to determine if patient characteristics or occupational therapy (OT) predict higher scores after rehabilitation. METHODS: In a prospective clinical cohort study, 109 patients with low vision completed the Impact of Vision Impairment (IVI) and the National Eye Institute Visual Functioning Questionnaire (NEI VFQ-25) before and after VR. Comprehensive VR included consultation with an ophthalmologist and OT if required. The relationships of six baseline characteristics (age, sex, visual acuity, contrast sensitivity, field loss, diagnosis) and OT were assessed with VRQoL scores using multivariable logistic regression. RESULTS: The mean (SD) age was 68.5 (19.2) years, and 61 (56%) were female. After rehabilitation, increases in scores were observed in all IVI subscales (reading [ P < .001], mobility [ P = .002], well-being [ P = .0003]) and all NEI VFQ-25 subscales (functional [ P = .01], socioemotional [ P = .003]). Those who were referred to OT but did not attend and those who had hemianopia/field loss were less likely to have higher VRQoL in IVI mobility and well-being. Those attending OT for more than 3 hours were less likely to have better scores in emotional NEI VFQ. Men were less likely to have increased scores in functional and emotional NEI VFQ, whereas those with diagnoses of nonmacular diseases had higher odds of having increased scores on the emotional NEI VFQ (all, P < .05). CONCLUSION: Both the IVI and the NEI VFQ-25 detected change in patients' VRQoL after rehabilitation. Most of the patient characteristics we considered predicted a lower likelihood of increased scores in VRQoL.